Reduced Dopamine D4 Receptor mRNA expression in lymphocytes among Malay Men undergoing methadone maintenance treatment. - Nur Khadijah, Muhamad Jamil; Nurul Asma, Abdullah; Imran, Ahmad; Ruzilawati, Abu Bakar (2019)
Background: Evidence has suggested that peripheral dopamine systems reflect central dopamine systems activity and pathology especially in neuropsychiatric diseases. Studies have been carried out widely on central dopamine systems, while investigation of dopamine system in various organ peripherally is still limited. It has been showed that peripheral blood lymphocytes express dopamine in peripheral system. Objective: In this study we investigated the difference Si dopamine receptors DRD4 and DRD5 mRNA expression in peripheral blood lymphocytes of ATS and opioid dependence undergoing methadone maintenance treatment and healthy Malay men subjects. Methodology: The dopamine receptors, DRD4 and DRD5 mRNA expression in peripheral blood lymphocytes were assessed by real-time PCR method. Results: The DRD4 mRNA expression level Is significantly reduced in lymphocytes population among ATS and opioid use disorder than in healthy control. However, the change of mRNA expression level of DRD5 was not statistically significant. Conclusion: In conclusion, patient undergoing methadone maintenance treatment may cause different effect on peripheral DRD4 and DROS mRNA expression.